2016
DOI: 10.1038/srep31347
|View full text |Cite|
|
Sign up to set email alerts
|

Comparative Transcriptome Analysis Identifies Candidate Genes Related to Skin Color Differentiation in Red Tilapia

Abstract: Red tilapia is becoming more popular for aquaculture production in China in recent years. However, the pigmentation differentiation in genetic breeding is the main problem limiting its development of commercial red tilapia culture and the genetic basis of skin color variation is still unknown. In this study, we conducted Illumina sequencing of transcriptome on three color variety red tilapia. A total of 224,895,758 reads were generated, resulting in 160,762 assembled contigs that were used as reference contigs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(69 citation statements)
references
References 46 publications
(51 reference statements)
2
64
0
Order By: Relevance
“…Red tilapia are known for their red colour, while the colour for Malaysian red tilapia varies from red to pink, pink/red and red with black spots (Zhu et al, ). In this study, all fish used for the experiment were pink at the start (whole pink body), whereas after 78 days of experiment changes in colour based on different photoperiods were observed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Red tilapia are known for their red colour, while the colour for Malaysian red tilapia varies from red to pink, pink/red and red with black spots (Zhu et al, ). In this study, all fish used for the experiment were pink at the start (whole pink body), whereas after 78 days of experiment changes in colour based on different photoperiods were observed.…”
Section: Discussionmentioning
confidence: 99%
“…However, red tilapia farming is challenged by pigmentation differences and colour variations especially during overwintering (Zhu et al, ). Luckily, previous studies established the melanogenesis pathway of Malaysian red tilapia and identified several key genes (such as tyrosinase [ tyr ], tyrosine‐related protein 1 [ tyrp‐1 ], solute carrier family 7 member 11 [ slc7a11 ] and SRY‐related HMG‐Box 10 [ sox 10 ]), which are involved in the process of melanin synthesis (Zhu et al, ). Moreover, the expression of slc7a11 and tyr genes involved in melanogenesis is re‐regulated by nutrition (Wang et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In evolutionary studies, analysis of transcript abundance is by far the most common functional genomic assay performed but many other factors can be measured including: DNA methylation, chromatin configuration, RNA splicing, RNA synthesis rate, protein-DNA interactions, histone modifications and enhancer-core promoter interactions (Bailey and Batailon, 2016;Zhu et al, 2016). Experimental approaches are now available to test the impact of functional gene changes on traits both at the molecular and organismal level (Turner et al, 2010).…”
Section: Genomic Approaches To Studying Evolution Of Phenotypic Traitsmentioning
confidence: 99%
“…Both phenotypic plasticity and genetic changes, in a complementary manner or independently, can contribute to this process (Jones et al, 2012;Kozak et al, 2014). Previous investigations have suggested that initial responses result from behavioral and/or phenotypic plasticity which is then followed by genetic assimilation (Wray, 2013;Feldman et al, 2016;Zhu et al, 2016). …”
Section: Introductionmentioning
confidence: 99%